Ayo and the Big Bullies - Akinfenwa, Funmi Joy (Nigeria, 2022)
This is a story about the adventures of Ayo and Amara who find themselves in Abuja, the capital of Nigeria. This story teaches children to speak up for themselves and their friends, and becomes allies instead of bystanders when bully occurs...
Keywords: Adventure; Bully; Juvenile Fiction